1976
DOI: 10.1104/pp.57.2.157
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Effects of Salinity and Phosphorus Nutrition of the Concentrations of Phosphate and Phosphate Esters in Mature Photosynthesizing Corn Leaves

Abstract: The effects of salinity on corn plants (Zea mays L.) are influenced by the concentration of nutrient orthophosphate. Salinity (-2 bars each of NaCI and CaCI2) was more injurious in combination with a high concentration of orthophosphate (2 mM) (that gave optimum yields in the absence of salinity) than it was with a lower concentration (0.1 mM). With 2 mm orthophosphate, salinity seemed to damage the plant mechanisms that normally regulate the internal concentration of orthophosphate resulting in excessive accu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
2

Year Published

1978
1978
2016
2016

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 93 publications
(46 citation statements)
references
References 24 publications
4
40
2
Order By: Relevance
“…In fact, salinity likely enhances P absorption (Roberts et al, 1984;Marschner, 1995;Navarro et al, 2001). However, toxic leaf P concentration can also be reached faster in plants grown in saline environments (Nieman and Clark, 1976;Grattan and Maas, 1984;Grattan and Grieve, 1999). On the other hand, P accumulation in salt-stressed plants could be a consequence of reduced translocation associated with a decreased demand for growth.…”
Section: Values Of F Testmentioning
confidence: 99%
“…In fact, salinity likely enhances P absorption (Roberts et al, 1984;Marschner, 1995;Navarro et al, 2001). However, toxic leaf P concentration can also be reached faster in plants grown in saline environments (Nieman and Clark, 1976;Grattan and Maas, 1984;Grattan and Grieve, 1999). On the other hand, P accumulation in salt-stressed plants could be a consequence of reduced translocation associated with a decreased demand for growth.…”
Section: Values Of F Testmentioning
confidence: 99%
“…2 mM vs. 2 mM). Several studies conducted in solution cultures have shown that P concentrations that are optimal in non-saline solutions may adversely affect growth or be toxic to corn (Bernstein et al, 1974;Nieman and Clark, 1976) as well as other agronomic crops grown under saline conditions. In these cases salinity by some unknown mechanism causes the plant to lose control of phosphate uptake (Roberts et al, 1984) and transport to the shoot.…”
Section: Phosphorusmentioning
confidence: 99%
“…However, much of the early research was conducted at rather high levels of [P] medium , leading to artefactual increases in P transport rates (see Nieman & Clark, 1976 ;Grattan & Maas, 1985). Contrarily, in some of the cases where only a moderate [PO % − ] medium was used, P transport was inhibited, especially in young shoot tissues.…”
Section: Anionic Nutrientsmentioning
confidence: 99%